Linking teacher preparation program design and implementation to outcomes for teachers and students - Carinci, Jennifer E.; Meyer, Stephen J.; Jackson, Cara (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2020)
Improving the use of evidence in teacher preparation is one of the greatest challenges and opportunities for our field. The chapters in this volume explore how data availability, quality, and use within and across preparation programs shed light on the structures, policies, and practices associated with high quality teacher preparation. Chapter authors take on critical questions about the connection between what takes place during teacher preparation and subsequent outcomes for teachers and students - which has remained a black box for too long. Despite a long history of teacher preparation in the U.S. and a considerable investment in preservice and in-service training, much is still to be learned about how pre-service preparation impacts teacher effectiveness.A strong empirical basis that informs how specific aspects of and approaches to teacher preparation relate to outcomes for graduates and their preK-12 student outcomes will provide a foundation for improved teaching and learning. Our book responds to stakeholders' collective responsibility to students and teachers to act more deliberately. Issues of data availability and quality, the uses of data for improvement, priorities for future research, and opportunities to promote evidence use in teacher preparation are discussed throughout the volume to inspire collective action to push the field towards more use of evidence. Chapters present research that uses a variety of research designs, methodologies, and data sources to explore important questions about the relationship between teacher preparation inputs and outcomes.
Keywords: Teachers -- Training of -- United States.; Education -- Study and teaching (Higher) -- United States.; Effective teaching -- United States.; Education -- Teacher Training & Certification.; Teacher training.; elektronické knihy; electronic books